Comparative Evaluation of Working Accuracy in the Atomic Diffusion Additive Manufacturing (ADAM) Process and the Binder Jetting (BJ) Process by Analysing Key Characteristics - Czan, Andrej; Czanova, Tatiana; Holubjak, Jozef; Novak, Martin; Czanova, Natalia; Czan, Andrej; Krisak, Dominik (Manufacturing Technology Journal, 2023)
This research focuses on comparing the working accuracy of two additive manufacturing processes, Atomic Diffusion Additive Manufacturing (ADAM) and Binder Jetting (BJ). Through the analysis of key characteristics of these processes, we aim to evaluate which one yields better results in terms of working accuracy. ADAM is a process that involves the gradual deposition of metallic materials using a plastic binder, whereas BJ is a process where the binder is applied to powder material, followed by the removal of excess binder. This work conducts a detailed examination of the properties of the ADAM and BJ processes, with a focus on surface texture and microstructure of the resulting objects, the use of optimal technological parameters, and the assessment of dimensional and shape accuracy. It is also important to note that the final nature of 3D objects depends on technological parameters such as geometry, orientation, and placement of individual shape specifications. The results of this study are crucial for assessing the accuracy of these additive processes and can serve as a significant basis for selecting an optimal approach in the field of additive manufacturing.
Keywords: Additive Manufacturing; Metal 3D Objects; Dimensional Accuracy; Shape Accuracy; Surface Roughness